2020
DOI: 10.1097/jnr.0000000000000381
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Positive Perceptions Toward Organizational Politics and the Work-Related Outcomes of Nurses

Abstract: Background Organizational politics (OP) exists to varying degrees in all organizations. OP plays an important role in creating synergy between employees and the goals of the organization. Purpose We aimed to investigate the relationship between positive perceptions toward OP and work-related outcomes in nurses, including stress level, burnout level, turnover intention, and job satisfaction. Methods This desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The results showed that organizational culture had an impact on job satisfaction and employee engagement. In a descriptive, analytical study, the group of authors (8) analyzed the relationship between the perception of organizational culture and the results with 280 nurses. The results showed that nurses did not perceive the organizational culture of healthcare facilities positively.…”
Section: Clinical Social Work and Health Intervention Vol 15 No 2 2024mentioning
confidence: 99%
“…The results showed that organizational culture had an impact on job satisfaction and employee engagement. In a descriptive, analytical study, the group of authors (8) analyzed the relationship between the perception of organizational culture and the results with 280 nurses. The results showed that nurses did not perceive the organizational culture of healthcare facilities positively.…”
Section: Clinical Social Work and Health Intervention Vol 15 No 2 2024mentioning
confidence: 99%
“…• qualitative studies from Canada, 21 Sweden, 22,23 and Finland; 24 • annual US professional surveys; 6,7,[25][26][27] • descriptive analytics from China 28 and Iran; 29 • a mixed-methods study from the United States; 30 • a nonexperimental study from the United States; 31 and…”
Section: Literature Reviewmentioning
confidence: 99%
“…The qualitative studies explored reasons why nurse specialists (ie, perioperative nurses and nurse anesthetists) chose to remain in a position 21,22 and reasons why nurse specialists resigned from a position 23 . Although most of the literature that we found described perioperative nurses’ intent to leave a position, 6,7,25‐27,29 none described the decision‐making processes for US perioperative nurses who resigned.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated reliability of the NSS with Cronbach alpha values reported at .82 (Hayes et al, 2015) and .89 with a test-retest reliability coefficient of .81 (Abuatiq & Borchardt, 2021). Validity of the NSS has been demonstrated, including content validity ratios >0.8 (Ezenwaji et al, 2019;Movahedi et al, 2020). While studies have indicated that the NSS is reliable and valid, it is unclear whether the NSS remains a comprehensive and accurate measure of occupational stress in current nursing practice.…”
mentioning
confidence: 99%